Students' Misconceptions towards Fraction Material Reviewed from the Level of Problem Skills - Ningrum, Rafika Cahya; N, Hepsi (Universitas PGRI Sumatera Barat, 2025)
This study aims to identify the types of misconceptions that occur in students in solving fraction problems. The research method used is descriptive qualitative with the research subjects being grade VI students of the 2024/2025 academic year at a school in Kosambi District, Tangerang Regency. The instruments used were written tests and interviews. The written test was in the form of questions about ordering fractions, while the interview aimed to explore the reasons behind the misconceptions made by students. The results of the study showed that the types of misconceptions that occurred were generalization, calculation, and notation misconceptions. These misconceptions were found in students with high, medium, and low ability levels. The analysis of the questions showed students' errors in ordering fractions based on their actual values, understanding the value of mixed fractions, and comparing fractions only based on the numerator or denominator without first equating the denominators. Factors causing misconceptions include lack of interest and motivation to learn, as well as ineffective learning methods. To overcome this misunderstanding, it is recommended that teachers provide a more in-depth explanation of the concept of fractions, use teaching aids, and relate the material to students' daily lives to make it more contextual.